Colors, patterns, and textures in nature - Joslin, Robert O.; West, Larry (Chicago : H. Regnery Co., 1974)
Over eighty color photographs introduce the diversity of color, patterns, and textures that appear in nature. Includes suggestions for nature study projects.
Keywords: Nature -- Juvenile literature; Nature